The Tip-Localized Phosphatidylserine Established by Arabidopsis ALA3 Is Crucial for Rab GTPase-Mediated Vesicle Trafficking and Pollen Tube Growth - Zhou, Yuelong; Yang, Yang; Niu, Yue; Fan, TingTing; Qian, Dong; Luo, Changxin; Shi, Yumei; Li, Shanwei; An, Lizhe; Xiang, Yun (The Plant cell, 2020)
RabA4 subfamily proteins, the key regulators of intracellular transport, are vital for tip growth of plant polar cells, but their unique distribution in the apical zone and role in vesicle targeting and trafficking in the tips remain poorly understood. Here, we found that loss of Arabidopsis ( ) AMINOPHOSPHOLIPID ATPASE 3 (ALA3) function resulted in a marked decrease in YFP-RabA4b/ RFP-RabA4d- and FM4-64-labeled vesicles from the inverted-cone zone of the pollen tube tip, misdistribution of certain intramembrane compartment markers, and an obvious increase in pollen tube width. Additionally, we revealed that phosphatidylserine (PS) was abundant in the inverted-cone zone of the apical pollen tube in wild-type Arabidopsis and was mainly colocalized with the trans-Golgi network/early endosome, certain post-Golgi compartments, and the plasma membrane. Loss of ALA3 function resulted in loss of polar localization of apical PS and significantly decreased PS distribution, suggesting that ALA3 is a key regulator for establishing and maintaining the polar localization of apical PS in pollen tubes. We further demonstrated that certain Rab GTPases colocalized with PS in vivo and bound to PS in vitro. Moreover, ALA3 and RabA4d collectively regulated pollen tube growth genetically. Thus, we propose that the tip-localized PS established by ALA3 is crucial for Rab GTPase-mediated vesicle targeting/trafficking and polar growth of pollen tubes in Arabidopsis.